2015
DOI: 10.1016/j.ccell.2015.09.018
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq of Tumor-Educated Platelets Enables Blood-Based Pan-Cancer, Multiclass, and Molecular Pathway Cancer Diagnostics

Abstract: SummaryTumor-educated blood platelets (TEPs) are implicated as central players in the systemic and local responses to tumor growth, thereby altering their RNA profile. We determined the diagnostic potential of TEPs by mRNA sequencing of 283 platelet samples. We distinguished 228 patients with localized and metastasized tumors from 55 healthy individuals with 96% accuracy. Across six different tumor types, the location of the primary tumor was correctly identified with 71% accuracy. Also, MET or HER2-positive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
806
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 719 publications
(864 citation statements)
references
References 68 publications
20
806
0
10
Order By: Relevance
“…This is consistent to the finding of CD34 expression in mature-appearing megakaryocytes in reactive and disorders of bone marrows (40), and increased ploidization of megakaryocytes has been reported in patients with metastatic tumors (43). Platelets, which are released from megakaryocytes in bone marrow, have recently been recognized to play an important role in cancer metastasis (44,45), and the gene expression profile of platelets has been shown to efficiently distinguish individuals with or without cancers (46). Platelet counts have also been investigated for cancer prognosis, and the data are still in conflict (47).…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent to the finding of CD34 expression in mature-appearing megakaryocytes in reactive and disorders of bone marrows (40), and increased ploidization of megakaryocytes has been reported in patients with metastatic tumors (43). Platelets, which are released from megakaryocytes in bone marrow, have recently been recognized to play an important role in cancer metastasis (44,45), and the gene expression profile of platelets has been shown to efficiently distinguish individuals with or without cancers (46). Platelet counts have also been investigated for cancer prognosis, and the data are still in conflict (47).…”
Section: Discussionsupporting
confidence: 88%
“…One additional limitation of RNA-based diagnostics appears to be that, unlike DNA, cell-free tumor RNA cannot be analyzed from the blood of tumor-bearing patients. However, a recent study suggests that blood platelets accumulate RNA molecules from cancer cells, enabling transcriptomic analyses for diagnostic purposes potentially using as little as a single drop of patient blood (30). Such technologies, when further validated, may be valuable to further elucidate the interplay between gene expression and oncogenic driver mutations in cancer.…”
Section: The Need For Clinical Standards For Transcriptomic Analysismentioning
confidence: 99%
“…This interaction affects the expression of relevant genes in tumor cells, but also alters the RNA profile of blood platelets (24,25). Cancer cells and the tumor microenvironment release signals that ultimately activate platelet surface receptors, induce specific splicing of pre-mRNAs in circulating platelets, and transform normal platelets to tumor educated platelets (TEP) (26). The combination of these splicing events, as well as the capacity of platelets to ingest circulating mRNA, provides TEPs with a dynamic RNA repertoire that can be used for cancer diagnostics.…”
Section: Novel Techniques On Cancer Researchmentioning
confidence: 99%
“…In addition, plateletderived RNA can be used for the real-time monitoring of ALK rearranged NSCLC patients treated with specific ALK inhibitors (31). Also, Thomas Wurdinger's group has demonstrated that TEPs can be successfully used for the detection of cancer among healthy individuals, and for identifying both the location of the primary tumor, as well as the genetic driver alteration among cancer patients (26). Specifically, they found that sequencing the mRNA from TEPs, distinguishes cancer patients from healthy individuals with 96% accuracy.…”
Section: Novel Techniques On Cancer Researchmentioning
confidence: 99%